Taxonomy of the genus Begonia (Begoniaceae) in Mindanao, Philippines III: New insights into the morphology and distribution of Begonia malindangensis and B. mindanaensis - Naive, Mark Arcebal K.; Cababan, Mc Arthur L.; Lubos, Lesley C.; Hughes, Mark (Phytotaxa, 2022)
Botanical excursions in the mountains of Bukidnon province, Mindanao resulted in the collection of two poorly known Philippine endemic Begonia species, B. malindangensis and B. mindanaensis. These two species are lectotypified and a comprehensive description, photographs, geographical distribution information and a preliminary IUCN conservation assessment are presented for each species.